The assessment and management of bycatch and discards in the South African demersal trawl fishery - Walmsley, Sarah Ann (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2005)
Over the past few decades it has become recognised that an ecosystem approach is required to manage world fisheries. Management strategies must ensure that non-target (bycatch) as well as target catches are sustainable. To achieve this, detailed commercial catch and biological information is required. The composition of catches made by trawlers operating off the south and west coasts of South Africa was investigated. Distinct fishing areas were identified on each coast, based on target species and fishing depth. Catch composition differed markedly among the areas defined. Although hake Merluccius sp. dominated South Coast catches, a large proportion of the catch was composed of bycatch. On the West Coast, hake dominated catches and this domination increased with increasing depth. On both coasts approximately 90% of the observed nominal catch was processed and landed. Estimates of annual discards suggested that the fishery discarded 38 thousand tons of fish per annum (16% of the nominal trawl catch). The data also indicated that hake discarding, the capture of linefish and the increased targeting of high value species might be cause for concern. Spatial analysis indicated that a variety of factors such as trawling position, catch size and catch composition affects bycatch dynamics. The monkfish Lophius vomerinus is a common bycatch species that has been increasingly targeted by demersal trawlers. This study showed that L. vomerinus is a slow-growing, long-lived species (West Coast males Lâˆž = 68.50cm TL, tâ‚€ = -1.69yr, K = 0.10yrâ »Â¹; West Coast females Lâˆž = 110.23cm TL, tâ‚€ = -1.54yr, K = 0.05yrâ »Â¹; South Coast sexes combined Lâˆž = 70.12cm TL, tâ‚€ = - 0.80yr, K = 0.11yrâ »Â¹), that matures at approximately 6 years of age. These traits could have serious management implications for the species. Per-recruit analysis suggested that the stock might be overexploited, although further investigation is required to confirm this. Solutions were suggested for each of the concerns raised, taking cognisance of the differences observed between the South and West Coasts and the economic dependence of South Coast companies on bycatch. The needs of future research were considered.
Keywords: Bycatches (Fisheries); Fishery management -- South Africa; Fisheries -- South Africa; Trawls and trawling -- South Africa